Spatial distribution of congenital syphilis in the state of Bahia, Brazil from 2009 to 2018 - Vital, Caroline Luz; Reis, Renato Barbosa; Soares, Jorgana Fernanda de Souza; Miranda, Diego Lopes Paim; Reis, Mitermayer Galvão (Frontiers in Epidemiology, 2023)
Objective To describe the temporal trend and spatial distribution of congenital syphilis (CS) cases in the state of Bahia, Brazil between 2009 and 2018. Method Mixed ecological study conducted through the analysis of data obtained from the Notifiable Diseases Information System and the Live Birth Information System. Global Moran Index I was performed in order to analyze spatial autocorrelation of CS cases in the municipalities of Bahia and the Local Spatial Association Indicator (LISA) was used to identify the formation of spatial regimes in the GeoDA software. Results 8,786 cases of CS were registered in the period. An increasing growth in CS incidence, with a 511% increase between 2009 and 2018. Spatial autocorrelation was observed between the municipalities (I Moran = 0.452; p < 0.001) and four clusters were identified. More frequently, mothers were aged 20–29 years (50.7%); had incomplete primary education (54.9%); were Black and multiracial (93.2%); received prenatal care (82.2%); 49.0% were diagnosed with syphilis during prenatal care; 68.8% were not adequately treated, and 81.1% of their partners were not treated. Conclusion The results showed that CS consolidates as a serious public health problem in Bahia, with an incidence 8.4 times higher in the period than the WHO target of 0.5/1,000 live births, predominantly related to inadequate prenatal care and social vulnerability indicators: young mothers with low education levels, as well as individuals identified as Black and multiracial. Thus, programs aimed at women of childbearing age and pregnant women need to be intensified.